Homero sob o olhar crítico da tradição (Nuntius Antiquus, 2008)
This article takes up the controversy concerning poets and thinkers against Homer and aims at showing that, in fact, both respect and disapproval towards Homer seem to be recurrent amongthem. Excerpts of Pindar, Hecateus, Herodotus, Thucydides, Xenophanes and Isocrates are analyzed, to show that this ambiguity regarding the poet existed permanently, long before even Plato's criticisms.